Public healthcare system utilization for chronic hepatitis C infection in Vietnam - Phuong Nguyen Thi Ngoc; Ngoc Nghiem My; Sabrina Rasheed; Fatema Khatun; Jennifer Van Nuil; Dung Nguyen Thanh; Hung Le Mạnh; Motiur Rahman (BMC Infectious Diseases, 2023)
Abstract Background Healthcare utilization is typically adversely affected when the treatment is expensive and requires multiple visits. We examined the determinants of healthcare-seeking for Hepatitis C virus (HCV) infection which is asymptomatic, chronic, and requires costly treatment in an urban tertiary care referral hospital in Vietnam. Methods We conducted a secondary analysis of hospital data for patients attending the Hospital for Tropical Diseases in Ho Chi Minh City, Vietnam between 2017 and 2020 specifically for HCV infection treatment. Poisson regression was used to determine the effect of personal factors (age, sex, comorbidities) and structural factors (health insurance, proximity to the facility, seasonality, year of visit) on the number of hospital visits. Results From 2017 to 2020 a total of 22,052 eligible patients sought treatment in the hospital. Among the patients, 50.4% were males and 58.7% were > 50 years of age. The mean number of visits per person was 2.17. In the multivariate analysis compared to 2017, the number of hospital visits increased by 4% in 2018 and then significantly decreased in 2019 and 2020. Visit numbers were significantly lower (6%) among South East region residents compared to those from Central Highlands and for those who lived further away from the hospital. The visit numbers were significantly higher among older age groups (5–11%), those with health insurance (6%), and those with comorbidities (5%) compared to others. Although the number of hospital visits by females was higher (7%) than males in 2017, it significantly decreased in subsequent years. Conclusions Our study indicated that there are both structural and individual factors affecting the number of visits for HCV treatment. To meet the global strategy for elimination of HCV, Vietnam Government needs to address the structural and personal barriers to healthcare seeking, with a special focus on women.